Nutritional composition and heavy metal content of the human placenta. (December 2017) - Chang, Sydney; Lodico, Laura; Williams, Zev
Abstract: Despite the vital and diverse roles of the placenta, remarkably little is known about its actual composition. Moreover, as placentophagy becomes increasingly popular, understanding the nutritional and heavy metal composition of the human placenta has practical implications. Here we evaluated the carbohydrate, sugar, protein, fat, cholesterol, vitamin, and heavy metal composition of the human placenta from uncomplicated singleton pregnancies and found that it contains a significant amount of cholesterol, protein, iron, and selenium, but no detectable levels of cadmium, arsenic, or mercury. Highlights: A nutritional label for the human placenta is presented. Human placenta contained a significant amount of cholesterol, protein, iron, and selenium. There were no detectable levels of cadmium, arsenic, and mercury in the placentas.